KATA MAJEMUK DALAM MAJALAH TIME (ANALISIS MORFOLOGIS) - Dondo, Alri Reiza; Lotulung, Donald R; Qarimah, Aryana N (Linguistika Kultura, 2025)
This study, entitled “Compound Words in Time Magazine (A Morphological Analysis),” aims to identify and classify the types of compound words found in Time magazine. A qualitative descriptive method is employed, and the data are analyzed using the theory of Carstairs-McCarthy (2002:59), which provides a framework for morphological analysis. The data consist of compound words taken from 26 articles in Time magazine. From the analysis, a total of 262 compound words are identified. These include 182 compound nouns, 3 compound verbs, 75 compound adjectives, 1 compound adverb, and 1 compound pronoun. The results indicate that compound nouns appear most frequently in journalistic writing, followed by compound adjectives. This study contributes to a better understanding of how compound words are used in journalistic texts and may serve as a reference for further morphological research or linguistic studies in media language.